ANALYSIS OF THE USE OF EDUCATIONAL MANAGEMENT IN IMPROVING CHILDREN'S RELIGIOUS CHARACTER AT BRILLIANT BUDS EDUKIDS KINDERGARTEN: Analisis Penggunaan Manajemen Pendidikan Dalam Meningkatkan Karakter Religius Anak di Tadika Brilliant Buds Edukids - Ardiansyah, Ryan; Pohan, Selamat (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the use of educational management in improving children's religious character at Tadika Brilliant Buds Edukids, Malaysia. Using a qualitative approach through observation and interviews, the study found that the application of educational management including planning, implementation, and evaluation can consistently create a conducive learning environment for the development of religious character in early childhood. Integration of religious values in learning, habituation of religious activities, and collaboration between teachers and parents are key factors for success. The main challenges faced are the diversity of children's backgrounds and the lack of parental involvement, but can be overcome with an adaptive and innovative approach. The results of this study are expected to be a reference in the development of religious character education in early childhood education institutions.